Diversification of Trash Fish Processing: The Impact of Composition on The Characteristics of Fish Balls in The Pasar Manna Region, South Bengkulu - Sari, Reni Nopita; Santoso, Joko; Sudarmo, Agnes Puspitasari (Hasanuddin University, 2024)
The production of trash fish from capture fisheries in South Bengkulu Regency is remarkably high but remains underutilised by the local community. Predominant trashfish species include peperek (Leiognathus bindus), senangin (Polynemus tetradactylum), and gulamah (Johnius trachycephalus). This study aims to evaluate the organoleptic, physical, and chemical characteristics of fish balls derived from trash fish through compositional experimentation. The research employed a randomised complete design (RCD) with seven product formulations and three replications. The study was conducted and tested at the Faculty of Agriculture Laboratory, Universitas Sriwijaya, from March to May 2024. The results revealed significant effects of multi-species fish ball compositions on moisture content, ash content, protein content, fat content, and whiteness degree. The gel strength testing showed a maximum gel strength of 138.73 g/cm². Furthermore, this research highlights that factors influencing the success of diversification strategies, including climate, freshness, trash fish species, production processes, ice addition, and raw material availability, could contribute to increased value and community welfare